2016
DOI: 10.1111/are.13081
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the survival, growth and gonad development of the diploid and triploid Hong Kong oyster, Crassostrea hongkongensis (Lam & Morton 2003)

Abstract: The Hong Kong oyster, Crassostrea hongkongensis is an economically important and widely cultivated oyster species in southern China. Aiming to improve the aquaculture potentials of C. hongkongensis, a triploid organism was generated by inhibiting the second polar body formation in the fertilized eggs, using 0.5 mg L−1 cytochalasin B. Triploids exhibited significantly higher growth and were larger than the diploids throughout the life cycle. Much of the triploid growth advantage can be attributed to resource re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…In our study, zygotes treated with hyperosmotic shock took more time to develop into D‐shaped larvae compared to the control zygotes. Similarly delayed development has also been observed in other induction methods (Chang et al, ; Y. H. Zhang et al, ; Zhao, ) and is a likely result of metabolic disruptions induced by the chemical or physical treatments. Mean shell length of D‐shaped larvae were longer after hyperosmotic treatment compared to the control larvae, as seen with hyposmotic shock (Zhao, ).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In our study, zygotes treated with hyperosmotic shock took more time to develop into D‐shaped larvae compared to the control zygotes. Similarly delayed development has also been observed in other induction methods (Chang et al, ; Y. H. Zhang et al, ; Zhao, ) and is a likely result of metabolic disruptions induced by the chemical or physical treatments. Mean shell length of D‐shaped larvae were longer after hyperosmotic treatment compared to the control larvae, as seen with hyposmotic shock (Zhao, ).…”
Section: Discussionsupporting
confidence: 59%
“…The triploid larvae were obtained using the optimal aforementioned induction parameters and cultured to the spat stage in 20,000‐L tanks. The larvae were fed with fresh Isochrysis galbana , as well as N. closterium and Platymonas subcordiformis, once the shell length reached 160 μm (Meng et al, ; Yang & Guo, ; Y. H. Zhang et al, ), and the quantity of algae was gradually increased from 2,000 to 80,000 cells/mL daily as the larvae grew (G. F. Zhang & Yan, ). The larval density was maintained at 5–6 larvae/mL at the D‐larval stage (Huo et al, ), and the swimming larvae were cultured at 15 ± 0.5°C with 2/3 water changes daily.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the controls had matured gonads from 180 to 450 days, suggesting that the spawning time of C. sikamea is longer than other oysters, including the Pacific oyster C. gigas in America (Allen & Downing, ), Sydney rock oyster in Australia (Cox et al, ), Eastern oyster in the Chesapeake Bay, United States (Dégremont et al, ), Pacific oyster in the west coast of Korea (Jeung, Keshavmurthy, Lim, Kim, & Choi, ), and Hong Kong oyster in the south coast of China (Zhang, Li, et al, ). C. sikamea is considered to be a subtropical species in China, has a long spawning period every year (Hu, Zhang, Wang, & Zhang, ), and the seasonal variation in reproduction is less evident than other oyster species living in colder areas.…”
Section: Discussionmentioning
confidence: 52%
“…Several studies on scallops have reported that triploidy induction does not affect larval growth rate in comparison to untreated controls (Barón et al., ; Toro et al., ). The larger size of adult triploid individuals in mollusks, compared to diploids, is mainly attributed to the effect of sexual sterility of triploids, which allows them to deflect the energy normally used for gonadal development and gamete production to somatic growth (Ruiz‐Verdugo, Racotta, et al., ; Zhang et al., ). In A. nucleus , gonad development is first observed when individuals are 3 months old, with a shell length between 20 and 25 mm (Velasco, ).…”
Section: Discussionmentioning
confidence: 99%
“…In mollusks, triploid individuals have three haploid chromosome complements, which results in a larger harvest size than diploid animals (Beaumont & Hoare, 2003). This effect has been mainly attributed to the total or partial sterility in triploid animals, which allows them to redirect the energy involved in reproduction to somatic growth (Ruiz-Verdugo, Racotta, & Ibarra, 2001;Wang, Guo, Allen, & Wang, 2002;Zhang et al, 2016). Triploidy in bivalves may be induced by DOI: 10.1111/are.13612 Patinopecten yessoensis (Meng et al, 2012;Yang, Li, & Guo, 2000), Pecten maximus (Beaumont, 1986), and Placopecten magellanicus (Desroisers et al, 1993).…”
Section: Introductionmentioning
confidence: 99%